The 2022 FIFA World Cup: Qatar’s Nation Branding to Promote Cultural Understanding in Post COVID-19 - Munzilin, Khairul; Nurhaliza, Afifa; Fatimatuzzahra, Ulya; Lathifa, Diva Nur (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This paper will examine Qatar's nation branding efforts during the 2022 FIFA World Cup mega event. With this aim, the focus of the analysis will lead to Qatar's strategy in carrying out nation branding and public diplomacy to bring the image and identity of Islam to the world community. Organizations like the FIFA World Cup are important milestones in history; therefore, the competition to host the World Cup is getting tougher, and Qatar makes history as the first Arab country in the Middle East to change the course of World Cup history. Overall, the World Cup in Qatar seems to have dispelled many myths and instilled a lot of kindness, respect, and hospitality when visiting a Muslim country. This paper uses the concept of nation branding from Simon Anholt. This research uses qualitative research methods with descriptive techniques. The findings of this paper are that: first, the implications of public diplomacy echoed by Qatar during the 2022 World Cup succeeded in breaking down the bad stigma and world stereotypes towards Islam; secondly, the state of Qatar contributes to clearly showing local Arab and Islamic culture and highlighting aspects of Arab-Islamic civilization to the world; and thirdly, The 2022 FIFA World Cup will be an extraordinary event with interests that are not only limited to football competitions but rather a manifestation of the goals that Qatar has set out in the Qatar National Vision 2030, which include economic diversification, support for environmental initiatives, human development, and social progress.